DIGITAL DIASPORA AND THE NEGOTIATION OF IDENTITY IN HUSSAIN’S HIDDEN FIRES (Contemporary Journal of Social Science Review, 2025)
This study explores identity negotiation from the perspective of the digital diaspora in the selected text, Hidden Fires. This study focuses on two main characters of the novel, Rubi and her grandfather, Yusuf. By applying the theoretical framework of Jennifer Brinkerhoff, Digital Diaspora: Identity and Transnational Engagement, this study uncovers the hidden realities of diaspora related to identity negotiation, homeland identity, self-positioning among youth, and psychological links with homeland. The analysis of this study highlights that migrants use social media platforms to maintain strong ties with their homeland, construct their position in the host society, and shape their identities. Hidden Fires is a perfect example of understanding the struggles of diaspora in relation to identity negotiation and homeland identity from the mirror of digital diaspora.